”Good neighbours are worth their weight in gold” – The role of familiarity on the revisit intention to neighbouring countries - Kökény, László; Szüle, Borbála; Birkner, Zoltán; Michalkó, Gábor (Hungarian Geographical Bulletin, 2025)
The aim of this study is to narrow down the research gap identified while uncovering the impact mechanism of destination familiarity on the revisit intention to the neighbouring countries. The research, justifies the hypothesis established based on the literature review by placing the analysis in the context of Hungary, located in the heart of East-Central Europe, and its relations with the seven neighbouring countries. In addition to the database of the Hungarian Central Statistical Office on the outbound travels of the Hungarian population, we build on the database of a survey conducted in 2023, with representative sampling, under which 400 Hungarian citizens with outbound travel experience were interviewed. The analysis was executed using simple and multivariate statistical methods. It was concluded that travellers of a non-neighbouring country perceive higher familiarity with the given destination, but it is not affecting more the revisit frequency than it is in a neighbouring country. The results will help to understand the tourist mobility between countries in a particular geopolitical situation due to the storms of history. The study highlights management implication and limitations; moreover, proposes directions for future research.